The miracle of flexibility : a head-to-toe program to increase strength, improve mobility, and become pain free - Esmonde-White, Miranda (Simon Element, 2023)
"Gain strength and mobility while living a pain-free life at any age using this revolutionary technique created by former ballerina, New York Times bestselling author, and star of PBS's Classical Stretch Miranda Esmonde-White"--